Persistence of drug therapy is associated with ischemic stroke and other vascular events in high-risk stroke population - Yi, Xingyang; Chen, Hong; Yu, Ming; Luo, Hua; Zhou, Ju; Wei, Wei; Wang, Yanfen; Chen, Xiaorong (Frontiers in Neurology, 2022)
The high-risk stroke populations are significantly associated with an increased risk of stroke or other vascular events. Although proven primary and secondary stroke prevention medications are available, persistent use is required to be effective. However, the persistence of drug therapy and its association with outcomes in the high-risk stroke population have received limited study in China. Hence, according to the China National Stroke Screening Survey (CNSSS) program in 2015, we performed this multicenter population-based cross-sectional survey and prospective cohort study in Sichuan of southwestern China. The residents aged ≥ 40 years volunteered to participate in a face-to-face survey in 8 communities. Subjects with at least three of eight stroke-related risk factors or a history of stroke were defined as high-risk stroke population. The interviewers recorded individuals' medications at a face-to-face survey, and all the high-risk stroke population was followed up for 4.7 years. The persistence of antihypertensives, hypoglycemics, lipid-lowering medications, and antithrombotics for stroke was evaluated. The primary outcome was new stroke. Secondary outcomes included new composite vascular events of stroke, myocardial infarction, and death during follow-up periods. Among 16,892 participants, 2,893 (17.1%) participants were high-risk stroke population and 2,698 (93.3%) participants completed to follow-up. The 4.7-year persistence of therapy rate of antihypertensives, hypoglycemics, lipid-lowering medications, and antithrombotics was 38.0%, 39.9%, 43.9%, and 59.8%, respectively. The total persistence of therapy rate for antihypertensives, hypoglycemics, lipid-lowering medications, and antithrombotics was 47.6% (136/286) in patients with hypertension, diabetes, dyslipidemia, and stroke at the same time. During the 4.7-year follow-up, there were 118 (4.4%) new ischemic stroke, 24 (0.9%) hemorrhagic stroke, 53 (2.0%) myocardial infarctions, and 33 (1.2%) deaths. After adjusting for the covariates, 4.7-year persistence of antihypertensives, hypoglycemics, lipid-lowering therapy, antithrombotics, and total persistence was independently associated with less new ischemic stroke and less new composite vascular events. Thus, more effective public education and efforts to understand and enhance the persistence of drug therapy are crucial to improve population health and decrease stroke and other vascular events for the high-risk stroke population.